PEMANFAATAN MODEL PEMBELAJARAN LANGSUNG DENGAN PENDEKATAN BERBASIS GENDER DI SMP ISLAM ALMAARIF 01 SINGOSARI - Ilma Qurrotul Aini; Muhammad Hanief; Devi Wahyu Ertanti (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
The purpose of this study is to describe about how the direct learning model with a gender-based approach, what factors underlie the learning model changes from ordinary classes into separate classes, and the benefits obtained from the application of direct learning models with a gender-based approach. The location of the study was located at Singosari Malang Almaarif 01 Middle School Jalan Ronggolawe No. 19 Singosari Malang. In this study the qualitative method was used, the document was obtained based on the results of interviews, observation, and documentation. Which is analyzed by data reduction, data presentation, conclusion drawing. The results of this study indicate that the direct learning model with a gender-based approach is a separate classroom atmosphere between male students and female students. with the hope that it can be one way to keep students from the opposite sex and familiarize good behaviors with the opposite sex also reduce the negative impact on relationships. While the approach in the direct learning model is teacher-centered, in this case the teacher delivers the contents of the subject matter in a very structured format, directs the activities of the students, and maintains the focus of academic achievement. Keywords: model, direct learning, gender.